Небо вокруг меня - Андреев Евгений Николаевич (Издательство ДОСААФ, 1983)
Экземпляры: КХ (20120405) / Инвентарный номер: 808267 / Цена: 0.30 / Сис.шифр: 796.2 / Авт.знак: А 65 / ГРНТИ: 77.29.31 / ББК: 75.724.7